Post-licensure safety monitoring of quadrivalent human papillomavirus vaccine in the Vaccine Adverse Event Reporting System (VAERS), 2009–2015. Issue 13 (20th March 2018) - Arana, Jorge E.; Harrington, Theresa; Cano, Maria; Lewis, Paige; Mba-Jonas, Adamma; Rongxia, Li; Stewart, Brock; Markowitz, Lauri E.; Shimabukuro, Tom T.
Abstract: Background: The Food and Drug Administration (FDA) approved quadrivalent human papillomavirus vaccine (4vHPV) for use in females and males aged 9–26 years, since 2006 and 2009 respectively. We characterized reports to the Vaccine Adverse Event Reporting System (VAERS), a US spontaneous reporting system, in females and males who received 4vHPV vaccination. Methods: We searched VAERS for US reports of adverse events (AEs) following 4vHPV from January 2009 through December 2015. Signs and symptoms were coded using Medical Dictionary for Regulatory Activities (MedDRA). We calculated reporting rates and conducted empirical Bayesian data mining to identify disproportional reports. Clinicians reviewed available information, including medical records, and reports of selected pre-specified conditions. Findings: VAERS received 19, 760 reports following 4vHPV; 60.2% in females, 17.2% in males, and in 22.6% sex was missing. Overall, 94.2% of reports were non-serious; dizziness, syncope and injection site reactions were commonly reported in both males and females. Headache, fatigue and nausea were commonly reported serious AEs. More than 60 million 4vHPV doses were distributed during the study period. Crude AE reporting rates were 327 reports per million 4vHPV doses distributed for all reports, and 19 per million for serious reports. Among 29 verified reports of death, there was no pattern of clustering of deaths by diagnosis, co-morbidities, age, or interval from vaccination to death. Interpretation: No new or unexpected safety concerns or reporting patterns of 4vHPV with clinically important AEs were detected. Safety profile of 4vHPV is consistent with data from pre-licensure trials and postmarketing safety data.